Ta có y = \frac{{3{{\left( {1 - {{\sin }^2}x} \right)}^2} + 4{{\sin
}^2}x}}{{3{{\sin }^4}x + 2\left( {1 - {{\sin }^2}x} \right)}}Đặt
\(t = {\sin ^2}x;0 \le t \le 2\). Khi đó y = \frac{{3{t^2} - 2t +
3}}{{3{t^2} - 2t + 2}} = 1 + \frac{1}{{3{t^2} - 2t + 2}}Xét hàm số f\left( t \right) = 3{t^2} - 2t + 2 (0 \le t \le 1)\Rightarrow f'\left( t \right) = 6t - 2 = 0 \Leftrightarrow t = \frac{1}{3}Ta có bảng biến thiên như hình vẽ:Suy ra \frac{5}{3} \le f\left( t \right) \le 3 \Leftrightarrow \frac{8}{5} \ge y \ge \frac{4}{3}Vậy \min y = \frac{4}{3}khi {\sin ^2}x = 1, chẳng hạn khi x = \frac{\pi }{2}\max y = \frac{8}{5}khi {\sin ^2}x = \frac{1}{3}
Ta có
y = \frac{{3{{\left( {1 - {{\sin }^2}x} \right)}^2} + 4{{\sin
}^2}x}}{{3{{\sin }^4}x + 2\left( {1 - {{\sin }^2}x} \right)}}Đặt
\(t = {\sin ^2}x;0 \le t \le
1\). Khi đó
y = \frac{{3{t^2} - 2t +
3}}{{3{t^2} - 2t + 2}} = 1 + \frac{1}{{3{t^2} - 2t + 2}}Xét hàm số
f\left( t \right) = 3{t^2} - 2t + 2 (0 \le t \le 1)\Rightarrow f'\left( t \right) = 6t - 2 = 0 \Leftrightarrow t = \frac{1}{3}Ta có bảng biến thiên như hình vẽ:Suy ra
\frac{5}{3} \le f\left( t \right) \le 3 \Leftrightarrow \frac{8}{5} \ge y \ge \frac{4}{3}Vậy
\min y = \frac{4}{3}khi
{\sin ^2}x = 1, chẳng hạn khi
x = \frac{\pi }{2}\max y = \frac{8}{5}khi
{\sin ^2}x = \frac{1}{3}